Obstacles of Parmusi Da'wah Communication in Border Areas - Usamah Hisyam; Sihabudin Noor; Novi Andayani Praptiningsih (Communication, 2023)
The purpose of this study was to find out the dynamics and problems of Parmusi's preaching communication on the NTT-Timor Leste border, Parmusi's efforts to overcome the problems of da'wah communication at the NTT-Timor Leste border, and Islamic quality improvement after the Da'i overcome the problem of da'wah communication on the NTT-Timor Leste border. The research method used is a qualitative approach with an interpretive research paradigm. The sources of primary data were obtained from observation, Focuss Group Discussion (FGD), interview with the mandalam on 6 (six) da'i Parmusi and 9 (nine) worshipers. Secondary data sources were obtained from the Qur'an & Hadist, documents and literature studies on journals, e-books, books, web, and online media. Data analysis techniques use the Interactive Model Miles & Huberman. The results showed that the dynamics and problems of da'wah communication in the NTT-Timor Leste border area are the lack of quantity of preachers, the low level of education and the religious quality of Muslims, especially converts, the lack of mosques which hinders congregational/Friday prayers. The activities of the Parmusi Da'wah Caravan in Rote Island and Kera Island, as well as the Rainmanuk subdistrict Belu, in the context of the inauguration of the construction of the Islamic Center and the formation of the Parmusi Madani Village running smoothly. Parmusi's efforts to overcome the problems of da'wah communication on the NTT-Timor Leste border are by increasing the preaching schedule through lectures, recitations and Friday sermons. Islamic quality improvement after the Da'i overcame the problem of da'wah communication on the NTT-Timor Leste border significantly increased. Many muslims pray in mosques, the recitation assemblies are crowded with worshipers, and converts are increasing in number.